2016
DOI: 10.1186/s12960-016-0171-2
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership, empowerment, and job satisfaction: the mediating role of employee empowerment

Abstract: BackgroundRecent studies have revealed that nursing staff turnover remains a major problem in emerging economies. In particular, nursing staff turnover in Malaysia remains high due to a lack of job satisfaction. Despite a shortage of healthcare staff, the Malaysian government plans to create 181 000 new healthcare jobs by 2020 through the Economic Transformation Programme (ETP). This study investigated the causal relationships among perceived transformational leadership, empowerment, and job satisfaction among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
154
0
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(223 citation statements)
references
References 68 publications
10
154
0
18
Order By: Relevance
“…The direct and indirect relationship between leadership and job satisfaction Based on the statistical analyses in the articles, it was found that empowerment mediated the effect of transformational leadership on job satisfaction in nursing teams, (8) as well as on authentic leadership and job satisfaction. (17) In another study, the indirect relationship between transformational leadership and job satisfaction took place through supervised support.…”
Section: Discussionmentioning
confidence: 99%
“…The direct and indirect relationship between leadership and job satisfaction Based on the statistical analyses in the articles, it was found that empowerment mediated the effect of transformational leadership on job satisfaction in nursing teams, (8) as well as on authentic leadership and job satisfaction. (17) In another study, the indirect relationship between transformational leadership and job satisfaction took place through supervised support.…”
Section: Discussionmentioning
confidence: 99%
“…Leaders are powerful wellsprings of organizational rents and consequently enhanced performance through sustainable competitive advantage (García‐Morales et al, , ) and managerial performance (Nguyen et al, ). This perspective indicates that transformational leadership will bring about large amounts of attachment, responsibility, trust, motivation, and performance in these new organizational situations (Hofman & Newman, ; Miao, Newman, & Huang, ; Zhu et al, ), job satisfaction (Choi, Goh, Adam, & Tan, ; De Clercq & Belausteguigoitia, ), employee engagement (Breevaart et al, ), and job involvement (Sheikh, Newman, & Azzeh, ) . Previous empirical studies have demonstrated that transformational leadership positively affects both individual productivity and organizational performance (Howell & Hall‐Merenda, ).…”
Section: Model and Research Hypothesesmentioning
confidence: 99%
“…2 Similarly, relational leadership styles that focus on creating positive relationships were associated with higher patient satisfaction, and reductions in patient mortality, medication errors, restraint use and hospital-acquired infections. 3 Although there is a proliferation of literature on leadership styles of nurse leaders, there is a dearth of studies focused on nurse leaders in Singapore.…”
Section: Introductionmentioning
confidence: 99%